PENERAPAN MODEL PEMBELAJARAN PROJECT-BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN KOLABORASI, KEMAMPUAN REGULASI DIRI, DAN KETERAMPILAN BERPIKIR KREATIF PADA PEMBELAJARAN BIOLOGI TOPIK PEMBELAHAN SEL PADA SISWA SMA KELAS XII IPA - Riak, Semuel; Hananto, Hananto (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Advances in science and technology have led to changes in people's needs to be able to respond to existing challenges. In the 21st century, education needs to develop various skills in students such as collaboration, self-regulation, and creative thinking. These skills in students of class XII IPA SMA XYZ North Jakarta are still low and need to be improved. This study aims to analyze the implementation of the Project-Based Learning model in teaching Biology on the topic of Cell Division in improving collaboration, self-regulation, and creative thinking skills for class XII IPA students at SMA XYZ Jakarta Utara. This study used the Classroom Action Research by Kemmis dan MC Taggart model which was carried out in three cycles where each cycle consisted of planning, observation, action, and reflection stages. The instrument to be used in this study is an assessment rubric to measure collaboration skills, self-regulation abilities, and creative thinking skills. The average score of collaboration skills in cycle one was 50.0, cycle two was 62.7, and cycle three was 88.9. The value of self-regulation ability in cycle one was 35.5, in cycle two was 52.4, and in cycle three was 88.1. Creative thinking skills in cycle one 46.0, cycle two 61.1, and cycle three 87.3. The data shows that the Project-Based Learning model can improve collaboration skills, self-regulation, and creative thinking in biology learning on the topic of cell division for class XII IPA students at XYZ School, North Jakarta.